Postoperative events and complications of next-day stent removal following uncomplicated percutaneous nephrolithotomy compared to longer stenting - Goodstein, Taylor; Mershon, Patrick; Posid, Tasha; Khuhro, Aliza; Charleton, Mary; Ndumele, Amara; Kleinguetl, Colin; Arnold, Chase; Knudsen, Bodo; Sourial, Michael W. (Canadian Urological Association Journal, 2023)
INTRODUCTION: Options for renal drainage after percutaneous nephrolithotomy (PCNL) vary and depend primarily on surgeon preference and case considerations. In our practice, patients traditionally returned one week postoperatively to remove the stents in the office via cystoscopy; however, following uncomplicated PCNL with no plans for second-look procedure, a ureteral stent on a tether is currently removed in tandem with the Foley catheter on postoperative day 1 (POD1) prior to patient discharge. This study compared the number of postoperative events between POD1 stent removal and their longer stented counterparts. METHODS: We conducted a retrospective chart review on all patients who had undergone PCNL at our institution from January 1, 2020, to June 31, 2021. Patient demographics, operative metrics, and postoperative events (telephone calls, emergency department [ED]/clinic visits, and complications) were recorded and compared between the two groups. RESULTS: A total of 243 patients were included in final analysis: 46% (n=111) had their stent removed on POD1 and 54% (n=132) had longer indwelling stent times. Baseline demographics were similar between the two groups. Number of telephone calls (p=0.081), ED/clinic visits (p=0.093), and complications (p=0.647) were similar between groups. There were three (1.3%) unplanned second-look procedures: two (1.8%) in the POD1 stent removal group and one (0.8%, p=0.475) in the later stent removal group. CONCLUSIONS: In this limited, retrospective study, we did not detect a difference in postoperative events or short-term complications for POD1 vs. later stent removal after uncomplicated PCNL.